Expansion of own revenue: analysis of the alternatives of the municipalities of the COREDE Rio Pardo Valley – RS - Bender, Reisoli Filho (2020)
The moment of economic instability imposes ever greater challenges to the management of municipalities, directly interfering in the tax collection. Based on this scenario, the objective of analyzing alternatives for the expansion of the own collection of the municipalities of the COREDE Rio Pardo Valley, from 2009 to 2016. Methodologically, it is a descriptive study, of a quanti-qualitative nature, whose approach method is analytical-comparative, applied to the analysis of the 23 municipalities that were stratified in three groups, according to the population range: group 3, municipalities with population less than 10,000 inhabitants; group 2, between 10,000 and 50,000 inhabitants and; group 1, over 50,000 inhabitants. The results showed that groups 2 and 3 have little expressive economic activity, basically rural, meaningless participation in the own collection, of 2.52 and 5.35%, respectively, precarious organizational structure of the tax sector and singular staff; in group 1, the municipalities are more economically structured and their own collection reached an average of 11.68%. In addition, it was found that the municipalities in groups 2 and 3 are in the initial phase of implementing actions, however they are seeking to leverage their own collection, even if, in the majority, the requirements standardized by the TCE/RS have not yet been adequate.